Study on the mechanical behaviour of Columnar Jointed Rock Mass under uniaxial compression state. Issue 7 (October 2021) - Xiang, Z P; Huang, S L; Wang, H L; Xu, W Y; Ding, X L; Yan, L; Liu, D X
Abstract: The columnar joint is a special type of primary joints which the cross sections are mostly quadrilateral, pentagonal and hexagonal. Intact rock mass is always cut by columnar joints into regular or irregular rock prisms, resulting in poor properties. With the expansion of large-scale engineering activities, a number of hydropower engineering such as Baihetan hydropower station, Xiluodu hydropower station and Ertan hydropower station, have encountered columnar jointed rock mass. The existence of columnar jointed rock mass poses a challenge to the design, construction and safe operation of these projects. To understand the mechanical behaviour of columnar jointed rock mass, uniaxial compression tests were carried out on artificial specimens made from rock-like materials. In the experiments, a self-designed pouring apparatus was used to prepare the columnar jointed rock-like specimens. Based on the experimental results of axial stress–axial strain curves, the strength and deformation of columnar jointed rock mass were investigated. The effect of columnar joint inclination angle on the mechanical behaviour of columnar jointed rock mass was analysed. It is found that the columnar jointed rock masses are characterized by significant anisotropy. The strength of columnar joint plays a significant role on the mechanical response of columnar jointed rock mass. The study Formatting the text